(untitled) (Tanzania Medical Journal, 2024)
Introduction Mental disorders such as depression are prevalent among People Living with HIV, and therefore health care providers need to be trained well to manage depressive symptoms. This study aimed to assess healthcare providers' knowledge, attitude, and practices in screening and managing depressive symptoms among people living with HIV (PLWH) attending the Care and Treatment Clinics (CTCs) in Dar es Salaam, Tanzania. Methods This was a cross-section study that employed a questionnaire to collect data. Convenient sampling was used to recruit 34 healthcare providers providing services at 23 public CTCs in Ubungo, Dar es Salaam. Data were analyzed using the SPSS program. Frequencies and percentages were run between the variables. Furthermore, in bivariate analysis, Pearson's Chi-square test was used to assess the association between independent and dependent variables. A p-value of < 0.005 was used to ascertain significant relationships between dependent and independent variables. Results This study revealed that healthcare providers (HCPs) had moderate knowledge of the management of depression in general. There were a few misconceptions about depression, as a vast majority agreed that depressed patients can break down at any time. The majority (64.7%) of the study respondents were trained on depression, and more than half (52.9%) were trained while in medical college. The majority (97.1%) of respondents knew the effectiveness of pharmacological and psychological approaches to treatment. In this study, the majority of respondents (97.1 %) had positive attitudes toward the management of depression, with females being significantly more likely than males to have a positive attitude (p =0.028). Moreover, many years of experience showed a positive significant association with knowledge about the management of depression in PLWH (p =0.002). Conclusion The majority of healthcare providers had moderate knowledge and positive attitudes toward the management of depression in PLWH. More years of work experience were associated with higher knowledge. Findings from this study highlight the need for healthcare providers and policy planners to increase knowledge and skills in screening depressive symptoms among PLWH at the CTCs.